Fostering ocean empathy through future scenarios. Issue 6 (4th September 2021) - Blythe, Jessica; Baird, Julia; Bennett, Nathan; Dale, Gillian; Nash, Kirsty L.; Pickering, Gary; Wabnitz, Colette C. C.
Abstract: Empathy for nature is considered a prerequisite for sustainable interactions with the biosphere. Yet to date, empirical research on how to stimulate empathy remains scarce. Here, we investigate whether future scenarios can promote greater empathy for the oceans. Using a pre‐post empathy questionnaire, participants ( N  = 269) were presented with an optimistic or a pessimistic future scenario for the high seas in a virtual reality (VR) or written format. Results showed that post‐test empathy levels were significantly higher than pre‐test levels, indicating that future scenarios fostered ocean empathy. We also find that the pessimistic scenario resulted in greater empathy levels compared to the optimistic scenario. Finally, we found no significant difference between the VR and written conditions and found that empathy scores significantly decreased 3 months after the initial intervention. As one of the first studies to empirically demonstrate the influence of a purposeful intervention to build ocean empathy, this article makes critical contributions to advancing research on future scenarios and offers a novel approach for supporting ocean sustainability. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.